2017
DOI: 10.1177/0892705717734599
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the impact effects of thermoplastic polyurethane reinforced with multi-walled carbon nanotube for soldier boot under the blast load

Abstract: The purpose of the study is to reduce the damage of the soldier boots, which subject the blast load. The boot sole was reinforced to perform the study. Thermoplastic polyurethane (TPU) and multi-walled carbon nanotube (MWCNT) materials were used for this reinforcement. In addition, TPU 508 material was used as energy absorber, and Carbon-Kevlar fiber composite was utilized to decrease the impact effect of blast load. Acceleration test system was used to simulate the blast load. Three different boots were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Solvent mixing technique 2334 was used for the synthesis of MWCNTs-reinforced PU composite material. Dimethyl formamide (DMF) solvent was used to dissolve PU and to disperse MWCNTs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solvent mixing technique 2334 was used for the synthesis of MWCNTs-reinforced PU composite material. Dimethyl formamide (DMF) solvent was used to dissolve PU and to disperse MWCNTs.…”
Section: Methodsmentioning
confidence: 99%
“…Mariappan and Jaisankar 22 performed thermal studies on SWCNTs-reinforced TPU composite material and reported improved melting and degradation temperature of the composite material. Doğru and Güzelbey 23 also prepared MWCNTs-reinforced TPU composite by varying the composition of MWCNTs and reported improved mechanical properties at a weight fraction of 1% MWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…So, there are many investigations that are showing this fact. Carbon/Epoxy [18][19][20][21][22][23][24], Glass/Epoxy-polyester [25][26][27][28], Kevlar/Epoxy-Vinylester [29][30][31][32][33][34][35][36][37][38][39][40] polymer composites are mainly studied ones. Among the fibers of the polymer matrix composites, Kevlar is an important material since this material type have high impact load absorbing capacities and have been an important researched fiber type.…”
Section: Introductionmentioning
confidence: 99%